A Case of Primary Pulmonary Meningioma Diagnosed by Bronchoscopic Biopsy - Masai, Kyohei; Nakagawa, Kazuo; Yoshida, Akihiko; Asakura, Keisuke; Motoi, Noriko; Tsuchida, Takaaki; Suzuki, Shigeki; Watanabe, Shun-ichi; Yoshida, Yukihiro (The Journal of the Japan Society for Respiratory Endoscopy, 2019)
Background. Primary pulmonary meningioma (PPM) is an extremely rare tumor derived from arachnoid cells that constitute the meningeal membrane. Case Report. A 60-year-old woman was referred to our hospital after an abnormal shadow, suspected to be lung cancer, was observed in her chest. Computed tomography revealed clear borders and a solid nodule in the right lower lobe, S10c. Bronchoscopic biopsy was performed using endobronchial ultrasonography with a guide-sheath (EBUS-GS) that was inserted into B10c, which was closest to the nodule. On hematoxylin and eosin (HE) staining, the tumor cells were found to be composed of neoplastic cells with abundant eosinophilic-to-clear cytoplasm and round-to-oval nuclei. The tumor cells did not show nuclear atypia. The tumor had a lobulated growth pattern with whorl formation and psammomatous bodies. Immunochemical staining revealed that the tumor cells were positive for epithelial membrane antigen (EMA) and progesterone receptor (PgR). On the basis of these findings, a diagnosis of PPM was made and right basal segmentectomy was performed. Conclusion. We report a rare case of PPM that we preoperatively diagnosed via bronchoscopic biopsy together with a literature review.